Makna Denotatif dsan Konotatif dalam Puisi Fakkir Bighairik Karya Mahmoud Darwish: Kajian Semantik - Muhammad Muhammad; Sayyed Zuhdi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study examines the denotative and connotative meanings in Mahmoud Darwish's poem "Fakkir Bighairik" using a semantic approach. Language as a sign system has a primary function in conveying meaning, and poetry is the medium of linguistic expression richest in such meaning. Darwish's poem, through dense diction, depicts empathy, humanity, and the struggle of the Palestinian people by inviting readers to "think of the other." This study uses a descriptive-qualitative method with library techniques, where data is taken from the text of Fakkir Bighairik's poem and analyzed based on the theory of denotative and connotative meaning. The results show that the denotative meaning in this poem conveys a direct and straightforward message, while the connotative meaning provides emotional, social, and moral depth that strengthens the humanitarian message. The combination of these two meanings creates a poetic effect that awakens readers' awareness of solidarity and universal human values. In addition, this poem also invites readers to reflect on their role in the humanitarian struggle and reminds them of the importance of fighting for human rights amidst conflict.